2019
DOI: 10.1587/elex.16.20190141
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of P-hit and N-hit single-event transient using heavy ion microbeam

Abstract: P-hit and N-hit single-event transients are investigated using heavy ion microbeam. A novel layout placement was implemented in the test chip to distinguish SETs originating from P-hit and N-hit. Experimental results indicate both the P-hit and N-hit SETs show an exponentiallike distribution in all target circuits. The SET cross sections and the average pulse width for P-hit and N-hit are also investigated. The well process, the transistor size and the layout topology significantly impact on the cross sections… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…The generation of soft errors caused by radiation-induced single-event transients (SET) is a significant reliability challenge in modern complementary metal-oxide-semiconductor (CMOS) logic, both in space applications and in terrestrial applications [1][2][3]. As process feature sizes continue to shrink, clock frequencies continue to increase, node capacitance and supply voltage decrease, the critical charge of transient pulses is reduced [3][4][5], and waveforms are more easily captured and soft errors are formed. It has been reported that SET are the main cause of soft errors in space applications [6,7], and charge sharing may even affect multiple nodes and cause single-event multiple transients (SEMT) [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The generation of soft errors caused by radiation-induced single-event transients (SET) is a significant reliability challenge in modern complementary metal-oxide-semiconductor (CMOS) logic, both in space applications and in terrestrial applications [1][2][3]. As process feature sizes continue to shrink, clock frequencies continue to increase, node capacitance and supply voltage decrease, the critical charge of transient pulses is reduced [3][4][5], and waveforms are more easily captured and soft errors are formed. It has been reported that SET are the main cause of soft errors in space applications [6,7], and charge sharing may even affect multiple nodes and cause single-event multiple transients (SEMT) [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…In Reference [14], pulse quenching can also affect SET. At the 65 nm process node, a lot of research has been done on the characterization of SET [3,[15][16][17][18], but in more advanced processes, the results of experimental measurements on SET are still few.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation